Towards Building a Navigation Profile for Emergency Response Vehicles by Analyzing Incident Callout Data - Aberle, Moritz (Proceedings of the International ISCRAM Conference, 2026)
The spatial coverage of units and resources is a key planning metric for emergency service operations. When computing isochrones for this purpose, the results depend heavily on the utilized navigation profile, which defines vehicle-specific parameters such as speed and routing restrictions. However, there does not yet exist a model for the specific driving characteristics of emergency vehicles. We analyzed historical incident callout data in the city of Freiburg im Breisgau to work towards developing such a model.